Effects of radiation on stability of triangular equilibrium points in elliptic restricted three body problem - Singh, Nutan; Narayan, Ashutosh (International Journal of Applied Mathematical Research, 2014)
This paper deals with the stability of triangular Lagrangian points in the elliptical restricted three body problem, under the effect of radiation pressure stemming from the more massive primary on the infinitesimal. We adopted a set of rotating pulsating axes centered at the centre of mass of the two primaries Sun and Jupiter. We have exploited method of averaging used by Grebenikov, throughout the analysis of stability of the system. The critical mass ratio depends on the radiation pressure, eccentricity and the range of stability decreases as the radiation parameter increases.   Keywords: Dynamical system, elliptical restricted three body problems, lagrangian points, radiation pressure, and stability.